A self-assembled nanoflower-like Ni5P4@NiSe2 heterostructure with hierarchical pores triggering high-efficiency electrocatalysis for Li–O2 batteries. (1st September 2022) - Han, Xue; Liang, Yanjie; Zhao, Lanling; Wang, Jun; Xia, Qing; Li, Deyuan; Liu, Yao; Zhou, Zhaorui; Long, Yuxin; Li, Yebing; Zhang, Yiming; Chou, Shulei
Abstract: The remarkably high theoretical energy densities of Li–O2 batteries have triggered tremendous efforts for next-generation conversion devices. Discovering efficient oxygen reduction reaction and oxygen evolution reaction (ORR/OER) bifunctional catalysts and revealing their internal structure-property relationships are crucial in developing high-performance Li–O2 batteries. Herein, we have prepared a nanoflower-like Ni5 P4 @NiSe2 heterostructure and employed it as a cathode catalyst for Li–O2 batteries. As expected, the three-dimensional biphasic Ni5 P4 @NiSe2 nanoflowers facilitated the exposure of adequate active moieties and provide sufficient space to store more discharge products. Moreover, the strong electron redistribution between Ni5 P4 and NiSe2 heterojunctions could result in the built-in electric fields, thus greatly facilitating the ORR/OER kinetics. Based on the above merits, the Ni5 P4 @NiSe2 heterostructure catalyst improved the catalytic performance of Li–O2 batteries and holds great promise in realizing their practical applications as well as inspiration for the design of other catalytic materials.